Narrativas inmersivas en aplicaciones móviles de geolocalización - Romero, Florencia Marina (2022)
Immersive narratives in the representation of virtual space in services that uses geolocation, specifically in services on mobile devices, pose a system of trust and replacement of the sense of orientation that used to be inherent to the human being. The construction of virtual images as a support for the generation of experiences in spatial orientation applications, such as Google Maps, breaks the limits between what has been considered a real image (linked to a present space-time) with the virtual representation of that image. The present work aims to the experience of users - considered in their diversity of perception / mobility possibilities - in urban areas, limited to the Autonomous City of Buenos Aires, and on how said construction influences their ways of inhabiting the cities. The objective is to analyze the generation of stories in the transit spaces of people in the Autonomous City of Buenos Aires in order to understand the dynamics of the modes of travel and create stories of the so-called non-places (Augé, 1992), specifically in public transport (subway, bus, bike path) and walking spaces.